Playing, social interaction and communication in the child with autism spectrum disorder - Galvão, Dulce Maria Pereira Garcia (2013)
Introduction: Every child plays. Playing is a fundamental right for all children with benefits in their motor, social and cognitive development. It is also an important tool to intervene in the child's health condition (Leite and Sandoval, 2003). The child with Autism Spectrum Disorder (ASD), which is a chronic and general disorder of children's development, has qualitative deficits in social interaction and communication, repetitive and stereotyped behavioral patterns and a restricted repertoire of interests and activities (Gadia et al, 2004; Fávero and Santos, 2005). Objectives: To identify how the child plays and the contribution of play to the promotion of social interaction and communication of children with ASD aged between two and ten years. Methods: Systematic review of full text papers published between January 2002 and July 2012 which included how ASD children aged between two and ten years old play. Web portals, databases and search engines were used (EBSCO, LILACS, PUBMED, MEDLINE, CINAHL, Academic Google). The following keywords in Portuguese, English and Spanish were used: "child", "autism", "ASD", "play", "communication" and "social interaction". Studies with ASD children with associated diseases were excluded. This search resulted in 834 papers: 84 were selected and 8 were used. Results: ASD children learn mostly through direct play (touch and use of objects). The use of some techniques such as repetition of the activity taught by the adult, social stories and reciprocal imitation in everyday playing can contribute to improving social interaction and developing language skills. Conclusion: Nurses should raise parents' awareness for the importance of playing in promoting social interaction and communication, which are often impaired in these children.